Steven-Johnson Syndrome - Pauline Joy F. Santos; Lauren Sylwanowicz (Journal of Education and Teaching in Emergency Medicine, 2017)
History of present illness: 72-year-old female with a history of hypertension and rheumatoid arthritis who presented to the emergency department (ED) with a chief complaint of rash for the past ten days. Her primary care provider prescribed azithromycin two weeks prior to her arrival in the ED for a sore throat. The rash started on her bilateral lower extremities and spread cephalad. She also noted a prodrome of subjective fevers and malaise.